Occurrence of Hepatitis E Virus in Pigs and Pork Cuts and Organs at the Time of Slaughter, Spain, 2017 - García, Nerea; Hernández, Marta; Gutierrez-Boada, Maialen; Valero, Antonio; Navarro, Alejandro; Muñoz-Chimeno, Milagros; Fernández-Manzano, Alvaro; Escobar, Franco Matías; Martínez, Irene; Bárcena, Carmen; González, Sergio; Avellón, Ana; et al. (Frontiers in Microbiology, 2020)
Zoonotic hepatitis E, mainly caused by hepatitis E virus (HEV) genotype (gt) 3, is a foodborne disease that has emerged in Europe in recent decades. The main animal reservoir for genotype 3 is domestic pigs. Pig liver and liver-derivates are considered the major risk products, and studies focused on the presence of HEV in pig muscles are scarce. The objective of the present study was to evaluate the presence of HEV in different organs and tissues of 45 apparently healthy pigs from 9 Spanish slaughterhouses (50% National production), that could enter into the food supply chain. Anti-HEV antibodies were evaluated in serum by an ELISA test. Ten samples from each animal were analyzed for the presence of HEV RNA by a RT-qPCR. The overall seroprevalence obtained was 73.3% (33/45). From the 450 samples analyzed a total of 26 RT-qPCR positive samples were identified in liver (7/45), faeces (6/45), kidney (5/45), heart (4/45), serum (3/45), and diaphragm (1/45). This is the first report on detection of HEV RNA in kidney and heart samples of naturally infected pigs. HEV RNA detection was negative for rib, bacon, lean ham and loin samples. These findings indicate that pig meat could be considered as a low risk material for foodborne HEV infection.